2005
DOI: 10.1111/j.1469-7610.2004.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic group, acculturation, and psychiatric problems in young immigrants

Abstract: There is a complex pattern of adaptation in cultural context and idiosyncratic relationships between distinct psychiatric symptom groups and socio-cultural factors. Information about the differentiated vulnerability of gender, generation, and ethnic groups to psychiatric morbidity is important to identify groups at special risk, and to produce interventions that are tailored to their needs. Future studies should examine how cultural factors contribute both to resilience and to an increased vulnerability to psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 85 publications
4
86
1
7
Order By: Relevance
“…Culture competence involves knowledge and skills about communication (both verbal and non-verbal) and about culturally embedded patterns of behavior and the values underlying these (Oppedal, Røysamb, & Sam, 2004;Oppedal, 2006). Earlier studies have shown associations between increasing levels of host (majority society) and ethnic (country of origin) culture competence and lower levels of internalizing and externalizing problems among adolescents with immigrant backgrounds beyond effects of socioeconomic status, length of stay and gender (Oppedal, Røysamb, & Sam, 2004;Oppedal, Røysamb, & Heyerdahl, 2005). Thus, they may be conceptualized as protective factors of mental health.…”
Section: Lack Of Consensus On the Construct Of Acculturationmentioning
confidence: 99%
“…Culture competence involves knowledge and skills about communication (both verbal and non-verbal) and about culturally embedded patterns of behavior and the values underlying these (Oppedal, Røysamb, & Sam, 2004;Oppedal, 2006). Earlier studies have shown associations between increasing levels of host (majority society) and ethnic (country of origin) culture competence and lower levels of internalizing and externalizing problems among adolescents with immigrant backgrounds beyond effects of socioeconomic status, length of stay and gender (Oppedal, Røysamb, & Sam, 2004;Oppedal, Røysamb, & Heyerdahl, 2005). Thus, they may be conceptualized as protective factors of mental health.…”
Section: Lack Of Consensus On the Construct Of Acculturationmentioning
confidence: 99%
“…The implications of migration for the mental health are widely accepted, and immigrants are classified as a high risk group for mental health problems [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…During exploration they may also seek contexts that are relevant for their ethnic identity, such as their ethnic or religious group. An achieved ethnic identity has been linked to a better psychological adjustment, whereas an ethnic identity crisis, where adolescents are unsure about their ethnic identity and unable to commit to any group, has been linked with externalising and internalising problems (Oppedal, Røysamb, & Heyerdahl, 2005).…”
Section: Building a Conceptual Frameworkmentioning
confidence: 99%